2015
DOI: 10.1155/2015/281263
|View full text |Cite
|
Sign up to set email alerts
|

The Combinational Polymorphisms ofORAI1Gene Are Associated with Preventive Models of Breast Cancer in the Taiwanese

Abstract: The ORAI calcium release-activated calcium modulator 1 (ORAI1) has been proven to be an important gene for breast cancer progression and metastasis. However, the protective association model between the single nucleotide polymorphisms (SNPs) of ORAI1 gene was not investigated. Based on a published data set of 345 female breast cancer patients and 290 female controls, we used a particle swarm optimization (PSO) algorithm to identify the possible protective models of breast cancer association in terms of the SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Our results showed that ORAI1-rs12320939 G>T was a protective variant against the risk of lung cancer, which is consistent with previous results in breast cancer (Ou-Yang et al, 2015). Rs12320939 G>T is an upstream transcript variant in ORAI1.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that ORAI1-rs12320939 G>T was a protective variant against the risk of lung cancer, which is consistent with previous results in breast cancer (Ou-Yang et al, 2015). Rs12320939 G>T is an upstream transcript variant in ORAI1.…”
Section: Discussionsupporting
confidence: 93%
“…The approaches of conventional statistics, machine learning, and data mining have been established to evaluate potential effects in GWAS association studies [24, 25, 5156]. Therefore, mathematical optimization algorithm of the OR-based method was applied to examine the susceptible risks of several cancers and disorders [23, 27, 28, 53, 55, 5759]. The strength of BPSO was used to ascertain the simulation-based association models with rapid and easy statistically analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both STIM1 and ORA11 express highly in breast cancer cells and their high expression are correlated with tumor aggressiveness and poor prognosis of breast cancers (131). In addition, three studies reported multiple SNPs of ORAI1 in breast cancers, which were predicted to associate with tumor malignancy (132)(133)(134). Overall, SOCE activation has been shown to promote breast cancer progression, especially via enhancing the tumor metastasis.…”
Section: Soce In Breast Cancersmentioning
confidence: 99%